2020
DOI: 10.1111/1471-0528.16427
|View full text |Cite
|
Sign up to set email alerts
|

Variants of uncertain significance in prenatal microarrays: a retrospective cohort study

Abstract: Objective To categorise the variants of uncertain significance found with prenatal chromosomal microarray and determine the proportion of such variants that are associated with a well-known phenotype in order to establish how often they remain truly of uncertain significance. Design Retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
5
9
1
Order By: Relevance
“…Our VUS prevalence of 7.0% was higher than some studies, 1,3,10–16,19,33,34 but comparable to 7.2% recorded in the Belgium national prenatal cohort 33 . The most common VUS in our study was the 15q11.2 deletion, which has a highly variable phenotype including neurodevelopmental delay, autism spectrum disorders, and obsessive‐compulsive disorders 35 .…”
Section: Discussionsupporting
confidence: 73%
“…Our VUS prevalence of 7.0% was higher than some studies, 1,3,10–16,19,33,34 but comparable to 7.2% recorded in the Belgium national prenatal cohort 33 . The most common VUS in our study was the 15q11.2 deletion, which has a highly variable phenotype including neurodevelopmental delay, autism spectrum disorders, and obsessive‐compulsive disorders 35 .…”
Section: Discussionsupporting
confidence: 73%
“…A considerable number of patients with SPGF (n = 28; 13%) carried large deletions and duplications spanning over 1 Mb, whereas the respective carrier frequency in the normozoospermic fertile men was two times lower (n = 4, 6.5%). The proportion of large CNVs in infertile men is in a similar range as reported for patients with autism 43 or DD 44 . In comparison, a study of 7,877 Estonian Biobank participants identified only 2% of subjects as carriers of > 1 Mb CNVs 27 .…”
Section: Discussionsupporting
confidence: 72%
“…This self‐selection of individuals with these traits pursuing this type of testing may initially falsely inflate the positive experiences of testing and receipt of results. Yet, at the same time, potential for uncertainty decreases (though is not eliminated) as the use of the new technology expands 26 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, at the same time, potential for uncertainty decreases (though is not eliminated) as the use of the new technology expands. 26 Participants frequently did not fully differentiate the technical differences of pGS from the other types of clinical genetic testing other than the additional waiting time and being more comprehensive. We also encountered this in a prior study of pES.…”
Section: Discussionmentioning
confidence: 99%